The Effect of Various Photoperiodic Conditions and Zn2+ Concentrations on Growth Rate and Metabolite Content in Euglena sp: Effect of Photoperiod and Zn2+ on Euglena sp. - Eko Agus Suyono; Budiman, Arief; Siti Ferniah, Rejeki; Astiti, Adam; Mardyansah, Deviko; Natalia, Fitri; Cindiati, Maya; Qonita Maghfiroh, Khusnul; Erfianti, Tia; Nurafifah, Istini; Amelia, Ria; Kurnianto, Dedy; Ryan Sadewo, Brilian; Maggandari, Revata (Journal of Tropical Life Science, 2024)
The application of Euglena as a carbon capture organism has generated considerable interest among scientists. Through the photosynthesis process, many kinds of metabolites are produced by Euglena, such as lipids, proteins, and pigments. Due to the metabolites produced by Euglena, it is vital to optimize the carbon capture ability and cell growth rate by adding Zn2+ content and giving photoperiodic into Euglena culture. The purpose of this study is to identify the optimal photoperiod and Zn2+ concentration to increase the growth rate, biomass, and metabolite content of Euglena sp. This study is a laboratory experiment involving the cultivation of Euglena sp. in various photoperiod cycles (light:dark), namely 24:0, 12:12, 14:10, and 16:8. In addition, Euglena sp. was also cultivated using different concentrations of Zn2+ (0 ppm, 5 ppm, 10 ppm, and 15 ppm). The growth of Euglena sp. was monitored for 18 days before being harvested every three days to measure the research parameters, including primary and secondary metabolites. The results showed that the photoperiod treatment and various concentrations of Zn2+ had a significant impact (P<0.05) on the growth rate, biomass, lipid, carbohydrate, protein, chlorophyll, and carotenoid levels of Euglena sp.